IKHTISAR SATU DEKADE KEMISKINAN DI NTT DALAM DIMENSI SOSIAL, EKONOMI, DAN INFRASTRUKTUR (ANALISIS REGRESI PANEL PADA DATA 2015-2024) - Abdul Rosyid Rexy Andryan (Badan Pusat Statistik Provinsi NTT, 2026)
Introduction/Main Objectives: The poverty in East Nusa Tenggara Province (NTT) over the past decade still shows a high number. The percentage of poverty in NTT is far above the national average and occupies the fourth highest position in Indonesia by 2025. Background Problems: This study explains the social, economic, and infrastructure factors in influencing poverty in NTT during 2015-2024. Novelty: This study uses time series data for poverty and possible variables that affect it in the last ten years by considering social, economic, and infrastructure dimensions. Long time series can provide more varied and efficient information whereas the panel data on the study better explains dynamic changes. Research Methods: The methods used in this research is panel data regressions which tests the panel data to find the best regression model. Finding/Results: The results of this study show that Labor Participations Rate (TPAK), average length of schooling, and per capita expenditure have a negative effect on poverty in NTT while life expectancy has a positive effect on poverty. The R-squared generated in the panel data regression model shows a figure of 74.95 percent so that it can explain the model well